The effect of processed soybeans and added energy in calf starters on the growth of Holstein calves - P. V. Reddy; J. L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1991)
In Trial 1, 91 Holstein calves were fed starters containing either soybean meal (SBM), extruded soybeans (ESB), roasted soybeans (RSB), SBM+soy oil (SO), or SBM+rumen inert fat (RIF) from birth to 10 wk of age. There were no differences in overall feed consumption, except that calves fed RSB consumed more than calves fed SBM+SO. There were no significant differences in weight gains, but calves fed SBM+SO tended to gain less. In trial 2, 71 Holstein calves were fed starters containing roasted soybeans from birth to 10 wk of age. Three of the starters contained 18% protein and soybeans roasted at 210, 260, or 290 F; the fourth starter contained 15% protein and soybeans roasted at 260 F. Calves fed starter containing soybeans roasted at 290 F consumed more feed, gained more weight, and were more efficient in converting feed and energy to gain than were the other calves fed 18% protein. Feed consumption was high and gains were intermediate by calves fed starter containing 15% protein. Growth in body size correlated with weight gains.; Dairy Day, 1991, Kansas State University, Manhattan, KS, 1991;
Keywords: Dairy Day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-175-S; Report of progress (Kansas Agricultural Experiment Station); 640; Dairy; Calves; Starter diets; Soybeans